1980
DOI: 10.1111/j.1432-1033.1980.tb04469.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Translation in vitro of Four Related Vitellogenin mRNAs of Estrogen-Stimulated Xenopus laevis

Abstract: Cloning of vitellogenin cDNA of Xenopus laevis revealed that vitellogenin is encoded in a small family of genes representing two distantly related main groups A and B, each comprising two more closely related subgroups A1, Az, and B1, BZ respectively. To characterize the proteins derived from these genes we have isolated the corresponding mRNAs by hybridizing, under stringent conditions, cytoplasmic poly(A)-containing RNA from the liver of estrogen-stimulated Xenopus to filter-bound cDNA clones containing sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
1
2

Year Published

1980
1980
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 21 publications
1
15
1
2
Order By: Relevance
“…Recently, several Vtg gene transcripts were discovered in the African clawed frog (VtgA1, A2, B1, B2) [74,75] and chicken (Vtg I, II, III) [76,77], along with fish species such as mummichog [78,79], barfin flounder [64], haddock Melanogrammus aeglefinus, a species of cod [80], tilapia Oreochromis aureus [81] and sheepshead minnow Cyprinodon variegatus, an estuarine-species of pupfish [82]. Among fishes, a gene encoding a special form of Vtg lacking the Pv region (phosvitinless Vtg, Pv-less Vtg) was first discovered in zebrafish Danio rerio [83].…”
Section: Multiplicity Of Fish Vitellogeninsmentioning
confidence: 99%
“…Recently, several Vtg gene transcripts were discovered in the African clawed frog (VtgA1, A2, B1, B2) [74,75] and chicken (Vtg I, II, III) [76,77], along with fish species such as mummichog [78,79], barfin flounder [64], haddock Melanogrammus aeglefinus, a species of cod [80], tilapia Oreochromis aureus [81] and sheepshead minnow Cyprinodon variegatus, an estuarine-species of pupfish [82]. Among fishes, a gene encoding a special form of Vtg lacking the Pv region (phosvitinless Vtg, Pv-less Vtg) was first discovered in zebrafish Danio rerio [83].…”
Section: Multiplicity Of Fish Vitellogeninsmentioning
confidence: 99%
“…The hybridization solution contained 105 cpm/cm2 of 32P-labelled cloned cDNA nick translated to a specific activity of 1-4 x 108 cpm/lg (17). In all cases, only cloned cDNA which had been isolated from the recombinant plasmid following S1 nuclease or Pst I digestion (17) was used. After hybridization the filters were washed twice at 370 C for 1 h in 50% formamide, 5 x SSC (1 x SSC: 150 mM NaCl, 15 mM trisodium citrate), 0.2% SDS, 0.1% sodium pyrophosphate and 10 pg/ml denatured calf thymus DNA and then twice at 370 C for 30 min in 2 x SSC, 0.2% SDS, 0.1% sodium pyrophosphate and 10 pg/ml denatured calf thymus DNA and then stringently at 37°C for 30 min in 50% formamide, 0.1 x SSC and 0.2% SDS.…”
Section: Determination Of the Extent Of Dnase I Digestionmentioning
confidence: 99%
“…The DNA was dissolved in 2 M urea, 40% formamide, 30 mM Tris-HCl pH 8.5, 1 mM EDTA, 40 Pg/ml of cytochrome C and spread onto distilled water as described (14 (16). The hybridization solution contained 105 cpm/cm2 of 32P-labelled cloned cDNA nick translated to a specific activity of 1-4 x 108 cpm/lg (17). In all cases, only cloned cDNA which had been isolated from the recombinant plasmid following S1 nuclease or Pst I digestion (17) was used.…”
Section: Determination Of the Extent Of Dnase I Digestionmentioning
confidence: 99%
“…vidual animals (10,11). Hybridization of cloned cDNA to Southern blots of uncloned genomic DNA digests showed that the different RNAs are transcribed from distinct genes (10).…”
mentioning
confidence: 99%
“…The filters were dried for 1 hr at room temperature, treated with alkali, neutralized, and baked for 6 hr at 800C. The filters were preincubated at room temperature for [10][11][12][13][14][15] hr in 50% formamide/0.6 M NaCI/200 mM Tris-HCl, pH 8.0/20 mM EDTA/0.1% sodium pyrophosphate/5 X Denhardt solution (17)/250,gg of E. coli tRNA per ml/100 tg of sheared denatured salmon sperm DNA per ml/0.2% sodium dodecyl sulfate (4 ml per filter). Vitellogenin cDNA clones (9,10) were used as hybridization probes after nick translation to a specific activity of 0.5-1 X 108 cpm/,ug (18).…”
mentioning
confidence: 99%